Candida Tropicalis renal microabscesses in a child with leukemia confirmed using nucleic acid amplification and recovery after prolonged antifungal and corticosteroid treatment. (April 2019) - Rosa Duque, Jaime S.; To, Kelvin K.W.; Chiang, Alan K.S.; Chan, Godfrey C.F.; Poon, Rosana W.S.; Yuen, Kwok-Yung; Ha, Shau-Yin; Cheuk, Daniel K.L.
Highlights: Disseminated Candida tropicalis can occur in leukemic patients undergoing chemotherapy. Candida tropicalis renal microabscesses can be detected nucleic acid amplification from ultrasound-guided aspirated fluid. The addition of corticosteroid may be useful in controlling immune reconstitution inflammatory syndrome for immunocompromised children. Abstract: We report the first case of microabscesses detected by polymerase chain reaction (PCR) amplification of nucleic acid from ultrasound-guided aspirated fluid in a three-year old boy with acute lymphoblastic leukemia and febrile neutropenia during induction chemotherapy. Fever persisted despite effective antifungal treatment. The addition of corticosteroid therapy successfully controlled the suspected immune reconstitution inflammatory syndrome (IRIS). This case highlights the utility of PCR and adjunctive corticosteroid in the approach of Candida tropicalis renal microabscesses in leukemic patients undergoing chemotherapy.